Zum Problem der Binnenlage der Republik Niger - Hetzel, Wolfgang (ERDKUNDE, 1970)
The Republic of Niger, like all the inland states of Africa which depend strongly on overseas trade, is faced with the problem of seeking or having to create an optimum route to the ports. This is not only a question of global transport costs, but concerns to whom and in what currency payments are to be made. In addition, political considerations have to be taken into account. The problem is heightened by the threefold imbalance which exists in the transport of export goods: (1) the volume of exported goods is much larger than the volume of imports, (2) there is a major discrepancy between the areas of origin of exports (East Niger) and the destination areas of imports (a large proportion to West Niger with the capital Niamey), (3) the transport demands in both directions are out of phase temporally. Apart from the Trans-Sahara route which can be discounted because of distance and technical difficulties, the Republic of Niger has three routes to the sea: via Ouagadougou to Abidjan (Ivory Coast), via Parakou to Cotonou (Dahomey) and via Kano to Lagos (Nigeria). When calculating transports costs not only the total distance is important but the extent to which the rail ways, the cheapest transport medium, can be used. The western areas of the Republic of Niger with Niamey belong to the ’natural’ hinterland of the port of Cotonou. In recent times, however, the Ivory Coast route has gained in competition with the Dahomey route. Although much longer it is not significantly more expensive to use. On the basis of global transport costs, Central and East Niger should be allocated to the hinterland of Lagos. This situation holds good for Central Niger (Maradi) since, despite the fact that Cotonou is just as near, the advantages of the railway to Lagos is vital for bulk exports of groundnuts. The point of equal transport costs to Lagos and Cotonou under present conditions lies, given the absence of State subsidies, in the area Birni - N’Konni - Madaona. Since 1953/54 not only the total (relatively small) groundnut exports of West Niger but also about one-fifth of the exports from Central and East Niger have been transported to Cotonou by the ’Organisation Commune Dahomey Niger’ (0. C. D. N.) in the ’Operation Hirondelle’. This operation also covers the import goods which come through Cotonou during the same period (about 1st November to about 15th May). The freight rates which customers have to pay to and from Central and East Niger are pegged at the rate for the Nigeria route; the difference which arises because of the higher costs of the Dahomey route is paid to transporters by the States of Dahomey and Niger. The operation is supplemented by a regulation of the transport between Cotonou and Niger during the rest of the year. This for all practical purposes, only affects West Niger; the eastern part of the country, outside the period of the ’Operation Hirondelle’ sends almost all its foreign trade traffic along the Nigeria route. The ’Operation Hirondelle’ has led to a marked improvement in groundnut export movements from Niger and has also contributed to the ability to overcome the difficulties arising from the events in Nigeria. The budget of the Republic of Nigeria is, however, almost unbearably burdened by it. Under normal conditions the attractive power of the Nigeria route would assert its dominance for East Niger. The reason for the ’Operation Hirondelle’ in the last resort can only be to maintain a possible competitive route to Cotonou for the area between Maradi and Zinder. An alteration in transport conditions e. g. through an extension of the railway from Parakou to Dosso, would naturally distort the transport cost relationships and thereby the economic boundary between port spheres of influence.